The Impact of Guided Inquiry Learning with Digital Swing Model on Students’ Generic Science Skill - Khoiri, N.; Huda, C.; Rusilowati, A.; Wiyanto, W.; Sulhadi, S.; Wicaksono, A. G. C. (Jurnal Pendidikan IPA Indonesia, 2020)
The low condition of students’ Generic Science Skills (GSS) becoming a concern since GSS is an essential provision for millennial living in the era of the industrial revolution 4.0. The study aimed to measure the impact of guided inquiry learning on generic science skills by using the digital swing model. This research used the experimental method which involved 360 students of 12th grade from senior high school. The primary data of students’ GSS were obtained from observations during activities and reports of practicum activities, then the resulting data were analyzed by t-test. The average of students’ GSS in the experimental class was 3.32, which is included in the very good category. Meanwhile in the control class was 3.17, which is included in the good category. Based on the results of the t-test analysis, the score was 0.044, which means that there were differences between the experimental class and the control class. Thus, it can be concluded that the use of digital swing has a positive impact on students’ GGS. The use of digital swing could stimulate the students to do the practicum activities which leads to the improvement of student’s GGS. However, this study is only focusing on the smaller angle; therefore, it is crucial for further research to set up the digital swing with the angle >15° to identify the effect on it.